(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The pharmaceutical care service provided by a home pharmacy is predicted to decrease theoccurrence of medication interactions and adverse effects, improve the efficacy of treatment, and boostpatient compliance with drug use. This study examined how the diabetic home pharmacy care programaffects pharmacies financially. The present study examined diabetic home pharmacy treatment costs. AsSaudi Arabia’s home pharmacy network manager, the pharmacist was here. A purposeful sample ofpharmacists was questioned after informed consent. The number of patients who must be treated inorder to break even after covering costs with revenue was determined. ABC was used to determine costbreakdown. Without home pharmacy care, Rp.17,000 to Rp.31,000 is the range. Average homepharmaceutical care cost Rp.9,963, but brought in Rp.22,000. The home pharmaceutical care programbenefits pharmacies, although pricing has not been established.